Tin Hội Nghị: Đại hội Hội Địa chất Thủy văn Quốc tế lần thứ XXXVIII tại Krakow, Ba Lan - Giảng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
1. GROUNDWATER QUALITY SUSTAINABILITY 1.1. Evaluation and management of groundwater - sustainable exploitation 1.2. Groundwater vulnerability and quality standards 1.3. Urban hydrogeology 1.4. Groundwater quality and agriculture 1.5. Groundwater quality and mining 1.6. Groundwater monitoring 1.7. Groundwater policy and legal aspects 1.8. Economic tools to protect groundwater 1.9. Sustainable management of groundwater 1.10. Decision support tools for sustainable groundwater management 2. GROUNDWATER AND DEPENDENT ECOSYSTEMS 2.1. Global climate change and water budget 2.2. Climate induced changes of land-use and their impacts on evolution of the EU Groundwater Directive 2.3. Interactions of surface and ground waters 2.4. Water in extreme conditions (arid and polar regions) 2.5. Wetland hydrology 2.6. Groundwater in eco-hydrology 2.7. Integrated groundwater management with dependent ecosystems 3. AQUIFER MANAGEMENT 3.1. Regional groundwater systems 3.2. Trans-boundary aquifers 3.3. Geophysical, geological and geochemical methods in groundwater exploration 3.4. Environmental and artificial tracers in hydrogeology 3.5. Social, ecological and economic implications 4. MINERAL AND THERMAL WATER 4.1. Geothermal resources 4.2. Origin of mineral and thermal waters 4.3. Hydrogeochemical characteristics of mineral and thermal waters 4.4. Social, ecological and economic implications 287 5. DATA PROCESSING IN HYDROGEOLOGY 5.1. Modelling as a tool of groundwater assessment 5.2. Groundwater flow and solute transport modelling 5.3. Groundwater mapping - approach and results 6. GENERAL HYDROGEOLOGICAL PROBLEMS 6.1. Hard rocks as specific media - methods and results 6.2. Hydrogeology of karst 6.3. Groundwater contamination - monitoring, risk assessment and restoration 6.4. Cost-effective measures to control and contain groundwater contamination 6.5. Risk-based groundwater management (brownfields, industrial/postindustrial and urban areas) 6.6. Coastal zone management 6.7. Managing aquifer recharge 6.8. Understanding and communication on groundwater - education and public involvement